(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article considers the peculiarities of innovations in the social sphere of commercial organizations, proposes a classification of innovations in the social sphere of a commercial organization. Management, organizational, educational and economic innovation directions were identified as the main result of the empirical study. Identify the scope of innovation in the enterprise. Identify the factors that are the reasons for the need to introduce changes, in particular: increase in profits and productivity, changes in society as a whole. Analyzed the reasons that promote and hinder the effective introduction of social changes, including insufficient motivation of staff and the preparation of managers for implementing change. Relevant forms of work for the implementation of psychological support for the process of introduction of changes are found. In our opinion, in order to improve the methods of implementing social innovations in commercial organizations, a clear understanding of the place of social innovations in the system of their innovation development is necessary. Moreover, an understanding of the structural and functional division of social innovations with a view to their conscious design and implementation, which will provide innovation-led result. In order to better understand the peculiarities of introducing innovations in the social sphere of organizations, we conducted an empirical study aimed at identifying the type of innovations in the social sphere of commercial organizations that are most commonly encountered at the moment, as well as factors that determine the necessity of introducing such innovations and the factors contributing to and impede the effective implementation of social change. The main purpose of our article is to study socio-psychological conditions for the implementation of social innovations in commercial organizations .The research carried out proved the fact of existing social innovation in modern commercial organizations. In addition: 1. In modern commercial organizations, the introduction of social changes that affect various spheres of the social environment of the organization, have an uneven distribution. In particular, the most innovative changes in the managerial, organizational, educational and economic component of the social environment of the organization. 2. Among the motives for introducing changes, the motive for gaining more profit, increasing productivity and satisfaction of employees with their work are the first place. An important place among the motives is also the compliance of the needs of employees with the new needs that arise in society as a whole. The biggest obstacles are ignoring the actual needs of employees and the formality of the changes introduced. 3. The initiators of such changes are, in most cases, the management of the company, which is guided by both the needs of a purely commercial nature and the requirements of modern changes in society. 4. The readiness of the employees to participate in the innovation processes and the conditions contributing to it, namely, the motivation of the personnel and the special training of the persons responsible for these processes are revealed. 5. It has been found that appropriate forms of work on the implementation of psychological support for the process of introducing changes are socio-psychological training and counseling, both group and individual. The prospects for further research are to analyze the readiness of the leaders of organizations to implement social changes, to develop practical ways of training employees and responsible for introducing changes in the social sphere of commercial organizations.